Menilai Prestasi Belajar melalui Penguatan Self Regulated Learning dan Kecerdasan Emosional Siswa pada Pembelajaran Matematika - Widodo Winarso; Deddy Supriady (Universitas Syiah Kuala, 2016)
Learning in school is a process which is complex and comprehensive. The existence of the learning process may make changes in the student, either intellectually or spiritual. The changes that occur are not only intellectually influenced by intelligence, but may also be with emotional intelligence and the ability to self regulated learning in learning. Associated with the condition, then the purpose of the research was to analyze the influence of the self regulated learning and emotional intelligence against the achievements of learning math students. This research was quantitative research with causal comparative method (ex post facto). The population in this research was all tenth-grade students at SMA 1 Susukan Cirebon. Based on Cluster sampling technique, we have chosen 36 students. Research instrument used was the assessment of self regulated learning, emotional intelligence of students, andthe learning of mathematics achievement test. As for the results of the research there was a positive influence between the self regulated learning againts achievement of learning math 0.819 or 81,9%, there was a positive influence between the emotional intelligence against the learning achievements of 0.742 or 74,2%, and there was a positive relationship between self regulated learning and emotional intelligence of students namely of 76.5%, meaning between both influence each otherwith regression equation was . The condition indicates that there was simultaneously influence among self regulated learning and emotional intelligence against the achievements of students learning math of 46,79%, and the rest was enough criteria 53.21% determined other factors.Learning in school is a process which is complex and comprehensive. The existence of the learning process may make changes in the student, either intellectually or spiritual. The changes that occur are not only intellectually influenced by intelligence, but may also be with emotional intelligence and the ability to self regulated learning in learning. Associated with the condition, then the purpose of the research was to analyze the influence of the self regulated learning and emotional intelligence against the achievements of learning math students. This research was quantitative research with causal comparative method (ex post facto). The population in this research was all tenth-grade students at SMA 1 Susukan Cirebon. Based on Cluster sampling technique, we have chosen 36 students. Research instrument used was the assessment of self regulated learning, emotional intelligence of students, andthe learning of mathematics achievement test. As for the results of the research there was a positive influence between the self regulated learning againts achievement of learning math 0.819 or 81,9%, there was a positive influence between the emotional intelligence against the learning achievements of 0.742 or 74,2%, and there was a positive relationship between self regulated learning and emotional intelligence of students namely of 76.5%, meaning between both influence each otherwith regression equation was . The condition indicates that there was simultaneously influence among self regulated learning and emotional intelligence against the achievements of students learning math of 46,79%, and the rest was enough criteria 53.21% determined other factors.